(untitled) (Altre Modernità, 2024)
This contribution aims to explore the evolution of the doctor-patient relationship along with the diaristic narration and the dystopian imprint that characterize "The Diary of the Rose" (1976), one of the most complex and penetrating stories from the collection The Compass Rose (1982), where the mastery and incredible talent of Ursula K. Le Guin compellingly stand out. If, on the one hand, it will be possible to approach the text thanks to the exegetical framework provided by dystopian science fiction, on the other hand, it will be necessary to implement this approach with the interpretative paradigms offered by the psychological humanities, emphasizing the existent dynamics between diagnosis, illness and treatment on the basis of the reversal of the doctor-patient roles.